2024
DOI: 10.1039/d4ea00002a
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-resolved quantum yields for vanillin photochemistry: self-reaction and ionic-strength implications for wildfire brown carbon lifetime

Greg T. Drozd,
Tate Weltzin,
Samuel Skiffington
et al.

Abstract: The light absorbing content of organic aerosol, brown carbon (BrC), directly affects climate and can play a role in the oxidative aging of organic aerosol. Recent estimates suggest that globally...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The uncertainties displayed correspond to one standard deviation of the three replicates. Furthermore, the linear flux assumption is made considering the equation described by Drozd et al, where the intensity is shown to affect the rate constant proportionally …”
Section: Experiments and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncertainties displayed correspond to one standard deviation of the three replicates. Furthermore, the linear flux assumption is made considering the equation described by Drozd et al, where the intensity is shown to affect the rate constant proportionally …”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Furthermore, the linear flux assumption is made considering the equation described by Drozd et al, where the intensity is shown to affect the rate constant proportionally. 43 Chemical Characterization. To perform the chemical characterization, two sets of experiments, i.e., 10 and 600 bar, were performed and analyzed after 3 h 30 min by UHPLC-DAD-ESI(±)-Orbitrap-MS.…”
Section: Experimental Setup and Sample Pressurizationmentioning
confidence: 99%